A method to map the interaction network of the nuclear lamina with genetically encoded photo-crosslinkers in vivo - Neumann-Staubitz, Petra; Kitsberg, Daniel; Buxboim, Amnon; Neumann, Heinz (Frontiers in Chemistry, 2022)
Lamins are intermediate filaments that assemble in a meshwork at the inner nuclear periphery of metazoan cells. The nuclear periphery fulfils important functions by providing stability to the nuclear membrane, connecting the cytoskeleton with chromatin, and participating in signal transduction. Mutations in lamins interfere with these functions and cause severe, phenotypically diverse diseases collectively referred to as laminopathies. The molecular consequences of these mutations are largely unclear but likely include alterations in lamin-protein and lamin-chromatin interactions. These interactions are challenging to study biochemically mainly because the lamina is resistant to high salt and detergent concentrations and IPs are susceptible to artefacts. Here, we used genetic code expansion to install photo-activated crosslinkers to capture direct lamin-protein interactions in vivo. Mapping the Ig-fold of laminC for interactions, we identified laminC-crosslink products with laminB1, LAP2 and TRIM28. We observed significant changes in the crosslink intensities between laminC mutants mimicking different phosphorylation states. Similarly, we found variations in laminC crosslink products intensities comparing asynchronous cells and cells synchronized in prophase. This method can be extended to other laminC domains or other lamins to reveal changes in their interactome as a result of mutations or cell cycle stages.